The strategic diagnosis of the potassium fertilizer industry in Brazil - PEDRO IGOR VEILLARD FARIAS; Estevão Freire; Armando Lucas Cherem da Cunha; Adelaide Maria de Souza Antunes (Journal of the Geological Survey of Brazil, 2021)
Fertilizers and crop nutrition play a key role in fulfilling the United Nations Sustainable Development Agenda. Brazil is the world’s fourth largest consumer of fertilizers. Between 1998 and 2018, the apparent consumption of potash fertilizers (in terms of K2O content) almost tripled, while the production of potassium chloride decreased in Brazil. Two important projects (Carnalita and Autazes) are still in the design phase, and there is considerable uncertainty surrounding them. Potassium producers located in Canada, Russia and Belarus have competitive advantages when compared to Brazil. The aim of this paper is to make a strategic diagnosis of the potassium fertilizer industry. The major variables that characterize the status of the Brazilian fertilizer industry could be identified, on the basis of data collected from annual business reports, reports from consulting firms, government websites, books, newspaper articles, sectoral studies and scientific articles. This paper concluded that, after detection of the current fragility of this sector, which is essential to the agribusiness production chain, public policies have to be formulated with a view to boosting this industry, based on the competitive advantages related to proximity to the Brazilian consumer market. However, there are disadvantages, namely, access to raw material, the need for infrastructure development and entry barriers caused by factors of scale and idle installed capacity in the major global players.